ROLE OF PROBIOTIC SUPPLEMENTATION ON CHILDREN WITH AUTISM SPECTRUM DISORDER - Dennis Ievan Hakim (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Introduction – Autism spectrum disorder (ASD) is one of the neglected problems which keep increasing worldwide and contributing high burden for the parents and sufferer. Currently, there are still no definitive or effective therapy existed. Probiotics are living beneficial microorganisms which can confer health benefits as management agent in ASD children. This paper will evaluate the role of probiotics as a promising management approach to ASD based on the novel knowledge thus increasing the patient’s quality of life. Methods – A literature review evaluating the role and effectiveness of probiotics in managing children with ASD is constructed with inclusion criteria based on PICOS framework. The article search strategy is using boolean operator with the main keyword “Autism Spectrum Disorder”, “Probiotic”, “Management” to get structured and specific results. Data extracted from Pubmed, ScienceDirect, and Cochrane databases with and only papers published from 2011-2021 that are included. Results – The author reviewed 8 articles that met inclusion criteria. Studies were conducted globally in children of various ages and the probiotic intervention varies in dose and durations. All studies stating that probiotics are effective to improve the symptoms of children with ASD. The Improvement is related to autism symptoms, gastrointestinal symptoms, microbiome variety, and laboratory findings. Discuss – The improvements by probiotics are correlated to some mechanisms including control of gut integrity, restore good microbiome variety, maturation of the host immune system, signaling to CNS via ENS, correcting “opioid excess”, and oxytocin maximization. Conclusion – Probiotic has a role in managing children with ASD by improving the symptoms based on the gut-brain axis approach. In future research, it is suggested to evaluate the long-term safety and efficacy and possible combination therapy of specific bacterial species of probiotic in clical trial research. Keywords: autism spectrum disorder, probiotic, management, supplementation.